2021
DOI: 10.1007/s00268-021-06082-8
|View full text |Cite
|
Sign up to set email alerts
|

Application of Real‐Time Augmented Reality Laparoscopic Navigation in Splenectomy for Massive Splenomegaly

Abstract: Objectives To evaluate the clinical impact and technical feasibility of augmented reality laparoscopic navigation (ARLN) system in laparoscopic splenectomy for massive splenomegaly. Methods The clinical data of 17 consecutive patients who underwent laparoscopic splenectomy using ARLN (ARLN group) and 26 patients without ARLN guidance (Non‐ARLN group) between January 2018 and April 2020 were enrolled. Propensity score matching (PSM) analysis was performed between the patients with and without ARLN guidance at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In a prospective cohort study comparing AR‐guided to standard laparoscopic splenectomy, 17 patients undergoing AR‐guided surgery had significantly lower intraoperative blood loss (306.6 ± 175.0 ml vs. 462.6 ± 300.5 ml, p = 0.047) and shorter inpatient stays (3.8 ± 1.3 days vs. 4.5 ± 2.6 days, p = 0.04) while operative times and rates of postoperative complications were not significantly different between the two groups 66 …”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…In a prospective cohort study comparing AR‐guided to standard laparoscopic splenectomy, 17 patients undergoing AR‐guided surgery had significantly lower intraoperative blood loss (306.6 ± 175.0 ml vs. 462.6 ± 300.5 ml, p = 0.047) and shorter inpatient stays (3.8 ± 1.3 days vs. 4.5 ± 2.6 days, p = 0.04) while operative times and rates of postoperative complications were not significantly different between the two groups 66 …”
Section: Resultsmentioning
confidence: 91%
“…However, in three other studies, AR systems showing only anatomy showed reduced blood loss with unchanged operative duration 50,60,66 . It might have been in these studies that AR guidance principally reduced error (and thereby tissue injury and blood loss) and had a lesser or no effect on speed (and operative duration), or that its potential effect on speed was negated by inexperience with new systems.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The field of laparoscopic imaging has evolved much through the efforts of various research groups in many areas, leading to advanced state-of-the-art systems including augmented/mixed reality capable systems [10][11][12][13][14][15][16][17][18][19][20][21][22][23], which further subdivides into hyperspectral imaging (HSI) systems [24][25][26][27][28][29][30][31][32][33][34][35] and combinatory operative imaging systems [36][37][38], dual/multi modal systems [39][40][41][42][43], and high speed hyperspectral systems [44]. Each system seeks to improve the current capabilities of surgical imaging in laparoscopic procedures by providing additional diagnostic data as well as methods for interpreting that data.…”
Section: Introductionmentioning
confidence: 99%